Repellent, antifeedant and insecticidal effects of neem oil on Microtheca punctigera - Mikami,Adriana Yatie (2008)
The effects of concentrations (0.00, 0.25, 0.50 and 1.00%) of the neem tree (Azadirachta indica - Meliaceae) oil emulsion on the behavioral and biological parameters of M. punctigera were investigated in the laboratory. Wild radish (Raphanus raphanistrum L.) host plant was used. Multiple and no-choice feeding preference assays were conducted which shown multiple effects. The males were repelled by the neem oil in multiple-choice assay. The adult (multiple-choice) and larvae (multiple and no-choice) feeding were deterred. The larvae mortality was higher in the neem oil treated than the control leaves. Further investigations are suggested to test neem oil in the management of the pest in the field.